HEAT PIPE INTEGRATION IN SOLAR PHOTOVOLTAIC/THERMAL (PV/T) SYSTEMS: A REVIEW OF DESIGN SYSTEM AND FUTURE OUTLOOK - Mochammad Resha (PT. Radja Intercontinental Publishing, 2025)
The integration of heat pipe technology into Solar Photovoltaic/Thermal (PV/T) systems presents a significant advancement for enhancing overall energy conversion efficiency by simultaneously generating electricity and recovering thermal energy. This review paper systematically examines the design, operational principles, performance, and future outlook of heat pipe-integrated PV/T systems. Heat pipes, as highly efficient passive two-phase heat transfer devices, effectively mitigate the critical issue of efficiency loss in PV modules caused by elevated operating temperatures. By utilizing internal evaporation-condensation cycles, they rapidly extract waste heat from PV cells, thereby lowering cell temperature, increasing electrical output, and enabling the recovery of useful thermal energy for applications such as water and space heating. The review categorizes and analyzes various heat pipe configurations, including conventional designs, Loop Heat Pipes (LHPs), and Pulsating Heat Pipes (PHPs), highlighting their respective advantages in terms of integration ease, long-distance heat transport, and high heat flux management. Despite their promising potential, key technological challenges such as thermal contact resistance, material compatibility, structural integrity, and economic viability are identified as barriers to widespread adoption. Future research directions emphasize the need for innovations in advanced materials (e.g., nanofluids), hybrid systems with Phase Change Materials (PCMs), optimized design through computational modeling, and the development of standardized testing protocols. Ultimately, heat pipe-integrated PV/T systems are poised to play a crucial role in the renewable energy transition, offering a compact, efficient, and sustainable solution for co-generation of electrical and thermal power.